2007
DOI: 10.1002/glia.20614
|View full text |Cite
|
Sign up to set email alerts
|

Developmental loss of NT‐3 in vivo results in reduced levels of myelin‐specific proteins, a reduced extent of myelination and increased apoptosis of Schwann cells

Abstract: This work investigates the role of NT-3 in peripheral myelination. Recent articles, based in vitro, propose that NT-3 acting through its high-affinity receptor TrkC may act to inhibit myelin formation by enhancing Schwann cell motility and/or migration. Here, we investigate this hypothesis in vivo by examining myelination formation in NT-3 mutant mice. On the day of birth, soon after the onset of myelination, axons showed normal ensheathment by Schwann cells, no change in the proportion of axons which had begu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
2
30
0
2
Order By: Relevance
“…BDNF promotes motor neuron survival and differentiation [54,55]. NT-3 supports myelin formation by enhancing SC motility and migration [56,57]. CNTF is a neuroprotective agent that facilitates remyelination [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF promotes motor neuron survival and differentiation [54,55]. NT-3 supports myelin formation by enhancing SC motility and migration [56,57]. CNTF is a neuroprotective agent that facilitates remyelination [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Latter studies found a promyelinating influence of NT3 via a proliferative response on oligodendrocyte progenitor cells (OPCs) (Xiao et al, 2009). Similarly, heterozygous knock outs of NT3 displayed a reduction in peripheral myelin mRNA and protein levels suggesting a promyelinating role for NT3 (Woolley et al, 2008). Myelination was also enhanced by transplantation of multi-neurotrophin-expressing glial-restricted precursor cells (GRPs) (Cao et al, 2005).…”
Section: Nt Treatment Increase Regeneration After Spinal Cord Injury mentioning
confidence: 99%
“…NGF enhances Schwann cell myelination of NGF-dependent neurons via activation of neuronal TrkA receptors but has no effect on BDNF-dependent neurons which do not express TrkA (Chan et al, 2004). NT-3 inhibits peripheral myelination in vitro (Chan et al, 2001;Cosgaya et al, 2002), whereas analysis of NT3Ϫ/Ϫ mice suggests it exerts a promyelinating influence (Woolley et al, 2008). BDNF enhances peripheral myelination during development and remyelination after injury (Zhang et al, 2000;Chan et al, 2001;Cosgaya et al, 2002;Song et al, 2006).…”
Section: Introductionmentioning
confidence: 99%